Internationally tradeable emission certificates: efficiency and equity in linking environmental protection with economic development - Udo E. Simonis (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 1996)
Three topics dominate the formulation an international greenhouse-gas regime as part of an effective global environmental policy. Efficiency, equity, and uncertainty. And three major policy instruments are discussed as regards the implementation of the 1992 Framework Convention on Climate Change: A carbon tax/C02-charge, joint implementation, and tradeable emission certificates. This paper tries to answer a question that has not been rigidly asked before: How could tradeable emission certificates be tailored in such a way as to be of benefit to the developing countries, to facilitate global environmental protection and economic development at the same time, and to meet both the efficiency and the equity criterion in international relations. Next to market organization and rules of procedure, allocation of the entitlements is crucial. The author suggests a dynamic formulae, by which the initial allocation of certificates starts on the basis of current greenhouse-gas emissions but over time turns towards equity in the form of equal per capita emissions. In this way, making emission entitlements tradeable among countries implies not only that a globally effective limit to total emissions is attained with certainty, but also that the current unfair allocation of emission entitlements is consecutively shifted in favour of the poor countries.
Keywords: 300